Volatility of by-product metal and mineral prices. (March 2016) - Redlinger, Michael; Eggert, Roderick
Abstract: Prices of by-product metals and minerals are often assumed to be inherently more volatile than prices of main and individual products. Yet there is limited analysis of their relative price volatilities. This paper applies regression analysis to compare the price volatility of by-product metals and minerals to commodities produced primarily or solely as main-products or individual products. This approach allows for estimating whether by-product supply is associated with greater price volatility and provides a framework for further research. By-products are found to have on average about 50% higher price volatility than main and individual products when evaluating annual prices over the last 50 years – although there are exceptions. However, when analyzing monthly prices over the past decade, the evidence that by-products have greater price volatility is mixed. Highlights: The price volatility of by-product metals is examined relative to main-products Annual prices of by-products have typically been more volatile over the past 50 years Evidence of higher volatility of monthly prices of by-products since 2005 is mixed